THE EFFECTIVENESS OF PROBLEM SOLVING MODEL WITH TATIGA CARDS TO THE LEARNING MOTIVATION AND INDEPENDENCE OF STUDENTS FOCUSING ON THE MATERIALS OF ANIMALS’ TISSUE - Sholikhah, Mona Ainun; Parmin, Parmin; Taufiq, Muhamad (Unnes Science Education Journal, 2017)
The aims of the research are to determine the effectiveness of problem-solving model with Media Tatiga Card to improve learning motivation and independence of animal tissue material students. The research method used is experiment with Nonequivalent Control Group Design. Sampling was done by cluster random sampling, with each experimental class and control class. Data were collected using documentation method, observation sheet, questionnaire and test. The results showed that the average score of learning motivation and independence of the experimental class students of each aspect into the category very well. The result of gain test analysis of cognitive learning outcomes of students in experimental class = 0.48 in the medium category, in control class of gain test result = 0.28 in the low category. The result of test analysis of difference of two means to the value of learning motivation obtained Pcount = 12,35, and test of difference of two average value of independence obtained Pcount = 12,43 with Ptable = 1,96. While the results of t test analysis of student learning outcomes show t count = 4.13 and t table = 1.67. It was concluded that the problem-solving learning model with the media of Tatiga Card is effective to improve the motivation of learning and independence of the students of grade VII SMP N 10 Magelang, Which is seen from the average score of learning motivation and independence of the experimental class students of each aspect in the category is very good, there are significant differences in learning motivation, student independence and learning outcomes between the experimental class and the control class.